Synthesis and characterization of silver nanoparticles impregnated polysaccharide derived network hydrogels by green protocol for use in biomedical applications - Sushil Kumar; Baljit Singh (Next Materials, 2025)
Recently, considerable growth has been attained in the fabrication of polysaccharide derived functional nano-materials for advanced biomedical purposes through environmentally conscious green protocols. Present study explored the potential of gum acacia (GA) for the generation of silver nanoparticles (AgNPs) and their subsequent impregnation into network hydrogels (HYD) prepared by grafting of 3-sulfopropylacrlate (SPA) onto GA and tragacanth gum (TG) to be applied in drug delivery (DD) systems. These NP-hydrogels were encapsulated with the antibiotic drug cephalexin to improve the therapeutic efficacy of (DD) carriers. Copolymers were characterized by UV-Vis, DLS, TEM, FE-SEM, AFM, XPS, FTIR, 13C NMR and TGA-DSC techniques. UV-Vis. indicated the formation of AgNPs at λmax of 435 nm. A Zeta potential of −18.9 mV was recorded for the colloidal solution of GA containing AgNPs referred to particle stability. TEM analysis revealed an average size 22.62 ± 7.81 nm with a uniform distribution of AgNPs. XPS peaks detected at 368 eV and 374 eV were attributed to the 3d5/2 and 3d3/2 binding energies of silver, respectively. Silver addition in polymer resulted in increase in mesh size (from 13.95 to 40.08 nm) of network structure which consequently enhanced the water absorption capacity of polymers (from 7.31 to 17.07 g/g of gel). pH sensitive drug release was facilitated by a polymer framework with a prolonged and sustained rate. The drug release was governed by a non-Fickian diffusion mechanism and release kinetics was described with First order kinetic model. DPPH assay of copolymers expressed 38.43 ± 2.07 % inhibition of free radicals while F-C reagent assay expressed anti oxidant activity of 34.79 ± 1.78 μg equivalent of gallic acid (GAE). Blood compatibility of polymers in terms of haemolysis (2.27 ± 0.24 %) and thrombogenicity (72.81 ± 4.45 %) illustrated their hemocompatible characteristics. Bio-adhesion measurements of polymers recorded the maximum force for detachment (107 ± 2 mN) during polymer interaction with mucosal membrane. Growth of E. coli, P. aeruginosa and S. aureus bacteria was inhibited by copolymers. These characteristic properties of copolymers make them ideal materials as DD carriers and biomedical applications.